On the competition between the stress-induced formation of martensite and dislocation plasticity during crack propagation in pseudoelastic NiTi shape memory alloys. Issue 23 (17th July 2017) - Ungár, Tamas; Frenzel, Jan; Gollerthan, Susanne; Ribárik, Gábor; Balogh, Levente; Eggeler, Gunther
Abstract: Abstract : The present work addresses the competition between dislocation plasticity and stress-induced martensitic transformations in crack affected regions of a pseudoelastic NiTi miniature compact tension specimen. For this purpose X-ray line profile analysis was performed after fracture to identify dislocation densities and remnant martensite volume fractions in regions along the crack path. Special emphasis was placed on characterizing sub fracture surface zones to obtain depth profiles. The stress affected zone in front of the crack-tip is interpreted in terms of a true plastic zone associated with dislocation plasticity and a pseudoelastic zone where stress-induced martensite can form. On unloading, most of the stress-induced martensite transforms back to austenite but a fraction of it is stabilized by dislocations in both, the irreversible martensite and the surrounding austenite phase. The largest volume fraction of the irreversible or remnant martensite along with the highest density of dislocations in this phase was found close to the primary crack-tip. With increasing distance from the primary crack-tip both, the dislocation density and the volume fraction of irreversible martensite decrease to lower values.